Identifikasi Morfometri Spermatozoa Sapi Simental dan Sapi Ongole - Jalius Jalius; Mustakim Mustakim; Fachroerrozi Hoesni; Bayu Rosadi; Farizal Farizal (Universitas Batanghari Jambi, 2023)
The aim of the research was to determine the morphometry comparison of spermatozoa of simental cattle and ongole cattle such as head length, head width, head area, middle piece length, tail length and overall body length. This research was carried out at the UPTD Laboratory of the Livestock Breeding Center, Horticulture and Animal Husbandry Food Crops Service, Jambi Province. This methodology uses exploration and observation of spermatozoa, using a microscope with a magnification of 400 times. The samples measured were 480 spermatozoa, taken from frozen semen randomly at the Department of Horticultural Food Crops and Livestock, Jambi Province, then smear preparations were made with eosin dye. The variables observed were head length (PK), head width (LK), head area (LKP), middle piece length (PMD), tail length (PE) and overall body length (PTK). The research results showed that the morphometry of simental cattle spermatozoa PK (9.46 µm), LK (5.11 µm), LKP (41.96 µm), MD (13.77 µm), PE (47.68 µm) and PTK ( 70.92 µm). Meanwhile, the size of the spermatozoa of Ongole cattle PK (9.48 µm), LK (5.17 µm), LKP (42.57 µm), MD (13.83 µm), PE (47.96 µm) and PTK (71.28 µm); The statistical results obtained were not significantly different in the morphology of the two cow spermatozoa. The relationship between PTK parameters of simental cattle spermatozoa and PE was very significant (r=0.870) and likewise for Ongole Cow Spermatozoa, the relationship between PTK and PE was very significant (r=0.953). This situation shows that there is a very close relationship between body length and tail length. The percentage of X chromosome simental cattle spermatozoa was (44.38%) and Y chromosome spermatozoa was (55.62%), while the percentage of X chromosome Ongole cattle spermatozoa was (45.83) and Y chromosome carrying spermatozoa was (54.17).